(untitled) (Journal of Economic Research & Business Administration, 2016)
Agriculture – is the most important economic activity, which plays a strategic role in the national economy , to ensure the production of food and raw materials for the processing industry in the required quantities and thus guarantee the country’s food security. The necessity of implementation of the administrative account at the enterprises of the agro-industrial complex. Identify the main advantages of the model of management accounting and offers a conceptual framework of the administrative account at the enterprises of agro industrial complex. A model structure of the centers of responsibility of agricultural producers for the organization of management accounting, which is a grouping them according to organizational and production structure of the economy, that allows you to link the activities of each department with the responsibility of individuals. In this scientific article reviewed major issues and problems of the organization of management accounting in agriculture and ways to solve them.